Metagenomic investigation of microbes and viruses in patients with jaw osteonecrosis associated with bisphosphonate therapy - Sedghizadeh, Parish P. (2012)
OBJECTIVE: The goal of this preliminary study was to use metagenomic approaches to investigate the taxonomic diversity of microorganisms in patients with bisphosphonate-related osteonecrosis of the jaw (BRONJ). STUDY DESIGN: Samples of saliva for planktonic microbial analysis and biofilm cultivation were collected from 10 patients (5 with BRONJ and 5 non-BRONJ control subjects) who met all ascertainment criteria. Prophage induction experiments—16S rRNA polymerase chain reaction and 454 pyrosequencing—and epifluorescent microscopy were performed for characterization and enumeration of microbes and viruses. RESULTS: Three phyla of microbes—Proteobacteria (70%), Firmicutes (26.9%), and Actinobacteria (1.95%)—dominated all BRONJ samples and accounted for almost 99% of the total data. Viral abundance was ~1 order of magnitude greater than microbial cell abundance and comprised mainly phage viruses. CONCLUSIONS: Individuals with jaw osteonecrosis harbored different microbial assemblages than nonaffected patients, and in general viral abundance and prophage induction increased with biofilm formation, suggesting that biofilm formation encouraged lysogenic interactions between viruses and microbial hosts and may contribute to pathogenicity.